Breaking expectations: Imagined affinities in mediated youth cultures. - Fogarty, Mary (Continuum: Journal of Media & Cultural Studies, 2012)
This article examines the mediated encounters experienced by participants in hip hop and funk dance styles especially breaking or b-boying/b-girling. It introduces the concept of imagined affinities to describe the spectrum of these encounters, which are enacted through mediated texts, or by travels through new places. Using interviews with dancers as a guide, I argue that artefacts made, distributed and circulated by dancers help to produce perceptions of commonalities between them. The nature of the process of rapid mediatisation, which has taken place during the past few decades, and its subsequent impact on breaking or b-boying/b-girling, are considered here through a concerted effort to historicize shifts in practice and experience. I examine the historical moment when homemade videotapes began to proliferate in the cultural practices of breaking, providing a source for the values and codes of hip hop culture. At that time, dancers on tour, who created the videos, celebrated the local contexts of other dancers from around the world while simultaneously showing a determination to appreciate breaking through its own practices and formats, even as these practices were becoming rapidly transformed and expanded through international networks.